Triglycerides as a predictor of cardiovascular risk: association with BNP and Troponin T in type 2 diabetes patients - Ilyas Khairi Hussein Ilyas, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Heart disease (CVD) is still the main reason people get sick and die. People with type 2 diabetes mellitus (T2DM) are more likely to get it because they have metabolic problems like insulin resistance, high cholesterol, and chronic inflammation. This study aims to discover how different body mass indexes (BMIs) of people with T2DM are linked to different levels of triglycerides, BNP, and Troponin T. This will help find out their risk of heart disease. Two hundred twenty-four people took part in the study. There were three groups based on their weight: those who were a healthy weight, those who were overweight, and those who were fat. The study found that Troponin T and cholesterol levels went up as BMI went up, but BNP levels went down. People who are overweight and have T2DM are more likely to get heart disease. There were the most triglycerides (175.0 ± 15.91 mg/dl) and Troponin T (0.22 ± 0.20 ng/ml) in the obese patients, but the least BNP (37.54 ± 1.68 pg/mL) compared to the normal weight and overweight patients. The results show that BNP levels and BMI are strongly linked in a bad way. Having more Troponin T and fat in the blood also shows that being overweight is hard on the heart. Low BMI, low reactive stress, and low cholesterol are all very important for people with T2DM to keep their heart health in check. If people in this high-risk group change how they live and use treatments that target oxidative stress and cholesterol metabolism, they may have fewer heart diseases and deaths.